CARE OVER THE INTERNATIONAL STUDENTS DURING COVID-19 LOCKDOWN - Bogusz, Marek (The Modern Higher Education Review, 2021)
This article is a diagnosis of the facts based on inner, empirical research. The aim of the Article is to present the situation of international students in WSG University during the lockdown related to the COVID-19 pandemic and the implemented measures and activities to counter its negative effects. The examples will relate to Poland and the university I represent. This article deals with the following issues: general situation of international students in Poland, brief overview of the university’s activities, what tools and procedures to adapt to the new situation were prepared in advance, and what should be implemented in a crisis situation, the challenges of a sudden increase in the level and quantity of distance learning and recruitment challenges of international students. The summary will be a presentation of good practices introduced at the university in the context of COVID-19, which can be implemented in many European universities.